Women in true crime media: the spectacle of female victims and perpetrators - Erdman, Jen (McFarland & Company, Inc., Publishers, 2022)
Sabella Nitti -- Bonnie Parker -- Elizabeth Short -- Marilyn Sheppard -- Sharon Tate -- Patricia Hearst -- Elizabeth "Liz" Kendall -- Kirsten Costas -- Nicole Brown -- Kathleen Peterson and Teresa Halbach -- Social media crimes.